Ross Procedure: How to Do It and How to Teach It. Issue 5 (September 2019) - Herrmann, Jeremy L.; Stram, Amanda R.; Brown, John W.
Prosthesis choice for aortic valve replacement (AVR) in children is frequently compromised by unavailability of prostheses in very small sizes, the lack of prosthetic valve growth, and risks associated with long-term anticoagulation. The Ross procedure with pulmonary valve autograft offers several advantages for pediatric and adult patients. We describe our current Ross AVR technique including replacement of the ascending aorta with a prosthetic graft. The procedure shown in the video involves an adult-sized male with a bicuspid aortic valve, mixed aortic stenosis and insufficiency, and a dilated ascending aorta.